COMPARATIVE STUDIES AND RELATIVE ABUNDANCE OF INSECT PESTS ASSOCIATED WITH STORED FOOD GRAINS IN GUSAU AND KAURA NAMODA MARKET AREAS, ZAMFARA STATE NIGERIA - M. T, ABDULAZEEZ; S.I., NA’ALA; M.M , MADAKI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Insect pests are one of the major challenges faced by grain farmers in Nigeria. These pests can cause significant damage to stored grain, resulting in significant economic losses for farmers and consumers alike. A comparative study was carried out to determine the relative abundance of Insect pests associated with stored food grains between Gusau and Kaura namoda Market areas of Zamfara state. Infested grains were sampled randomly from stores within the Market Areas. In Gusau markets, the relative abundance of a total of 2,612 insect pests was observed to be associated with stored food grains, comprising 494 (19%) millet grains, 1106 (42%) maize grains, 187 (7%) rice grains and 825 (44%) of cowpea seeds. While in Kaura namoda markets, a total of 1,121 insect pests were observed to be associated with 140 (13%) millet grains, 290 (26%) maize grains, 197 (18%) rice grains, and 494 (44%) cowpea seed were recorded. Maize grains stored in both markets surveyed were observed with the highest rate of infestation 1,396 (55%) while Rice grains had the least rate of infestation 384 (25%). Insect pests’ rate of infestations were higher in Gusau markets (2,612) than in Kaura namoda markets (1,396). Farmers and businessmen should be enlightened on improved storage practices, particularly in Gusau market, and further research is needed to improve our understanding of insect pest biology and behavior and to develop new and sustainable strategies for controlling these pests in stored food grains.